2016
DOI: 10.1159/000454735
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Extravesical Submucosal Tunneling Ureteroneocystostomy Combined with Psoas Hitch for Medium-Length Distal Ureteral Defects in Adults

Abstract: Objective: This study aims to describe the technique and feasibility of laparoscopic submucosal tunneling ureteroneocystostomy in combination with psoas hitch to restore urinary tract continuity in patients showing medium-length distal ureteral defects. Materials and Methods: From January 2012 to April 2016, a total of 13 patients (4 males and 9 females) with a mean age of 37 years were performed with the laparoscopic operation of ureteral submucosal tunneling reimplantation combined with psoas hitch. The mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The psoas hitch procedure has so far been performed predominantly with an open approach. However, case series ranging from 9 to 18 patients, 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 and one prospective cohort study of endometriosis patients (psoas hitch n = 94), 30 reported on the feasibility of laparoscopic and robot‐assisted psoas hitch procedures with outcomes comparable to open surgery. For future research on psoas hitch procedures performed with a laparoscopic or robotic approach, our advice is to carry out effective follow‐up and documentation of patients in whom a psoas hitch is performed, in order to be better able to assess the long‐term results of the psoas hitch procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The psoas hitch procedure has so far been performed predominantly with an open approach. However, case series ranging from 9 to 18 patients, 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 and one prospective cohort study of endometriosis patients (psoas hitch n = 94), 30 reported on the feasibility of laparoscopic and robot‐assisted psoas hitch procedures with outcomes comparable to open surgery. For future research on psoas hitch procedures performed with a laparoscopic or robotic approach, our advice is to carry out effective follow‐up and documentation of patients in whom a psoas hitch is performed, in order to be better able to assess the long‐term results of the psoas hitch procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical interventions, such as reimplantation of the ureter with psoas hitch, Boari lap or ureteroneocystostomy will re-establish drainage of urine from the kidney [1][2][3]. Creation of an orthotopic sigmoid neobladder will likewise effectively correct the obstruction and prevent permanent damage to renal function [4].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, with the wide adoption of minimally invasive techniques in urology, ureteral reimplantation (UR) has experienced a transition from open to laparoscopic and robotic approach. Compared to OUR, minimally invasive approach is associated with less blood loss, reduced postoperative analgesic consumption, and shorter hospital stay while yielding similar clinical outcomes [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%